Prognostic Significance of Tumor-Associated Macrophage Content in Head and Neck Squamous Cell Carcinoma: A Meta-Analysis - Kumar, Ayan Tyagi; Knops, Alexander; Swendseid, Brian; Martinez-Outschoom, Ubaldo; Harshyne, Larry; Philp, Nancy; Rodeck, Ulrich; Luginbuhl, Adam; Cognetti, David; Johnson, Jennifer; Curry, Joseph (Frontiers in Oncology, 2019)
Background: Head and neck squamous cell carcinoma (HNSCC) exists within a microenvironment rich in immune cells. Macrophages are particularly abundant in and around tumor tissue, and have been implicated in the growth, malignancy, and persistence of HNSCC (1). However, current literature reports variable degrees of association between the density of tumor-associated macrophages (TAMs) and clinicopathologic markers of disease (2, 3). These inconsistent findings may be a result of differences in approach to TAM detection. Authors have measured total TAMs in tumor tissue, while others have stained tumor samples for individual subtypes of TAMs, which include pro-inflammatory (M1-like) and immunosuppressive (M2-like). Our aim is to more clearly define the prognostic significance of the phenotypes of tumor-associated macrophages in HNSCC. Methods: We conducted a meta-analysis of the existing publications investigating the relationship between TAMs (total and M2-like subtype) and T stage, nodal involvement, vascular invasion, lymphatic invasion, and tumor differentiation (Figure 1). A total of 12 studies were included. Forest plots and risk ratios were generated to report overall effect. Results: Higher density of both total and M2-like subtype of TAMs in the tumor microenvironment is associated with advanced T stage, increased rates of nodal positivity, presence of vascular invasion, and presence of lymphatic invasion (p < 0.0001; Figures 2–9). There is no significant association between TAM density, either total or M2-like subtype, and tumor differentiation (Figures 10, 11). Conclusions: Increased density of TAMs, including those of the M2-like phenotype, correlate with poor clinicopathologic markers in HNSCC. Our findings warrant additional investigation into the subpopulations of TAMs, the mechanisms behind their recruitment and differentiation, and the associated influence of each phenotype on tumor growth and invasion. A greater understanding of TAM dynamics in HNSCC is critical for directing further research and employing TAM-targeted adjunct therapies.